A PROSPECTIVE STUDY OF URINARY TRACT INFECTION IN CHILDREN WITH NEPHROTIC SYNDROME IN A TERTIARY CARE HOSPITAL - Dr.T.Santoshini Devi, Dr Lelsani Poorna Chandra Rao, Dr.K.Bheemeshwar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Nephrotic syndrome characterized by the presence of heavy proteinuria,hypoalbuminemia, edema and hyperlipidemia, is a common renal disorder in pediatricpopulation. In developed countries, its incidence is20 to 40 and 20 to 70 per million populationsin UK and USA respectively, whereas in Asian countries it is 90 to 160 per million populations.